2015
DOI: 10.1152/japplphysiol.00594.2015
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis-related ultrastructural changes to capillaries in human skeletal muscle in response to endurance exercise

Abstract: The ultrastructure of capillaries in skeletal muscle was morphometrically assessed in vastus lateralis muscle (VL) biopsies taken before and after exercise from 22 participants of two training studies. In study 1 (8 wk of ergometer training), light microscopy revealed capillary-fiber (C/F) ratio (+27%) and capillary density (+16%) to be higher (P ≤ 0.05) in postexercise biopsies than in preexercise biopsies from all 10 participants. In study 2 (6 mo of moderate running), C/F ratio and capillary density were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 36 publications
8
56
2
Order By: Relevance
“…All biopsies were taken from the participants at rest within a 6-wk period. Specimens were chemically fixed in a 6.25% (vol/vol) glutaraldehyde solution buffered with 0.1 M sodium cacodylate HCl (pH 7.4) and stored at 4°C until analysis (9).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All biopsies were taken from the participants at rest within a 6-wk period. Specimens were chemically fixed in a 6.25% (vol/vol) glutaraldehyde solution buffered with 0.1 M sodium cacodylate HCl (pH 7.4) and stored at 4°C until analysis (9).…”
Section: Methodsmentioning
confidence: 99%
“…With the use of these light micrographs, the number of capillary profiles and that of muscle fibers were quantified using the forbidden line rule (52). The mean cross-sectional fiber area (MCSFA) was estimated by point counting, and capillary profile density and capillary-to-fiber (C/F) ratio were calculated, as described previously (9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that pericytes in human skeletal muscle proliferate/mobilize in response to exercise-induced angiogenesis with a significant increase in pericyte density, thickness, and endothelial coverage and a concurrent decrease in basement membrane density and thickness in ultrastructural analyses of capillaries in human muscle biopsies (Baum et al, 2015). Furthermore skeletal muscle pericytes are also considered to be myogenic precursors distinct from satellite cells, themselves thought to be the primary source of postnatal myoblasts (Zammit et al, 2006).…”
Section: Function In Muscle Development and Homeostasismentioning
confidence: 99%
“…ASP has various bioactivities, such as hematopoiesis, immunomodulation, radioprotection, and anti-tumor activity [9,10]. And previous study indicated that angelica sinensis suppressed nitric oxide (NO) and prostaglandin E secretions in vitro.…”
Section: Accepted Manuscriptmentioning
confidence: 99%